Developing English modules with integrated Islamic values and the Jambi local wisdom - Uyun Nafiah (Universitas Syiah Kuala, 2020)
Since studies about integrating Islamic values and local wisdom, especially in the Jambi context, have been scarcely found in the literature, this research is aimed to investigate the integration of such values in the English module that is suitable and practical for high school students. This developmental research used ADDIE approach which consists of five stages: analyze, design, develop, implement and evaluate. The sample for this study was an English teacher and 38 students of class IX of at one of the Islamic junior high school in Jambi by using instrument interviews, observation, and questionnaires. Based on the result of the validity questionnaire by two expert validators, a mean percentage of 82.07% is obtained and categorized as very valid. The result of students’ practicality questionnaire shows a percentage of 83.86% and categorized as very practical. Meanwhile, the result of teachers’ practicality is 87.50%, and also categorized as very practical. It could be concluded that the integrated Islamic values and Jambi local wisdom on the English module is suitable, practical and beneficial for both students and teacher. The researcher further recommends using this module for teaching English, especially for the procedure text type as discussed in the paper.